Antimicrobial Polymers of Linear and Bottlebrush Architecture: Probing the Membrane Interaction and Physicochemical Properties. Issue 19 (24th June 2022) - Bapolisi, Alain Murhimalika; Kielb, Patrycja; Bekir, Marek; Lehnen, Anne‐Catherine; Radon, Christin; Laroque, Sophie; Wendler, Petra; Müller‐Werkmeister, Henrike M.; Hartlieb, Matthias
Abstract: Polymeric antimicrobial peptide mimics are a promising alternative for the future management of the daunting problems associated with antimicrobial resistance. However, the development of successful antimicrobial polymers (APs) requires careful control of factors such as amphiphilic balance, molecular weight, dispersity, sequence, and architecture. While most of the earlier developed APs focus on random linear copolymers, the development of APs with advanced architectures proves to be more potent. It is recently developed multivalent bottlebrush APs with improved antibacterial and hemocompatibility profiles, outperforming their linear counterparts. Understanding the rationale behind the outstanding biological activity of these newly developed antimicrobials is vital to further improving their performance. This work investigates the physicochemical properties governing the differences in activity between linear and bottlebrush architectures using various spectroscopic and microscopic techniques. Linear copolymers are more solvated, thermo‐responsive, and possess facial amphiphilicity resulting in random aggregations when interacting with liposomes mimicking Escheria coli membranes. The bottlebrush copolymers adopt a more stable secondary conformation in aqueous solution in comparison to linear copolymers, conferring rapid and more specific binding mechanism to membranes. The advantageous physicochemical properties of the bottlebrush topology seem to be a determinant factor in the activity of these promising APs. Abstract : Polymers architecture plays an important role in the structure–activity relationship of antimicrobial polymers. Comprehensive spectroscopic and microscopic methods are used to analyze the physicochemical properties of linear and bottlebrush copolymers and their mechanism of interaction with membranes. The stable secondary conformation of multivalent bottlebrush copolymers explains the more efficient mechanism of interaction with bacterial membranes compared to linear counterpart.